2020
DOI: 10.1002/cncy.22303
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of double‐reading cytology smears as a triage strategy among high‐risk human papillomavirus–positive women in Mexico

Abstract: BACKGROUND: The goal of this study was to determine whether the detection of histologically confirmed cases of cervical high-grade squamous intraepithelial lesions or worse (HSIL+) can be increased by having each liquid-based cytology (LBC) slide read by 2 cytotechnologists as part of routine screening. METHODS: Over 36,212 women aged 30 to 64 years participated in the Forwarding Research for Improved Detection and Access for Cervical Cancer Screening and Triage (FRIDA) Study in Mexico between 2013 and 2016. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…A study conducted in Mexico reported that 3,914 women with positive high-risk HPV were triaged with liquid-based cytology. The study detected a 20.9% increase in HSIL+ cases when double reading was done ( 62 ).…”
Section: Recent Developments In Screening Methodsmentioning
confidence: 93%
“…A study conducted in Mexico reported that 3,914 women with positive high-risk HPV were triaged with liquid-based cytology. The study detected a 20.9% increase in HSIL+ cases when double reading was done ( 62 ).…”
Section: Recent Developments In Screening Methodsmentioning
confidence: 93%
“…A double reading of these slides was employed to adjudicate the cytological result, as previously described 22 . For all cytological examinations, both the cytotechnologists and the cytopathologist were aware that specimens were hrHPV positives, but they were blinded to HPV16/18 result.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have documented greater acceptability of the SeCUS and an increase in the participation of women who do not regularly attend screening programs, and SeCUS is a low-cost procedure [ 8 , 11 , 15 ]. This finding supports the proposal that the SeCUS may be regarded as an acceptable alternative for collecting primary samples for cervical cancer screening, thereby increasing screening coverage for women who resist cervical sample collection [ 11 ].…”
Section: Introductionmentioning
confidence: 99%